Genetic diversity and population structure of Amorphophallus albus, a plant species with extremely small populations (PSESP) endemic to dry-hot valley of Jinsha River - Rong Tang; Erxi Liu; Yazhou Zhang; Johann Schinnerl; Weibang Sun; Gao Chen (BMC Genetics, 2020)
Abstract Background Amorphophallus albus P. Y. Liu & J. F. Chen (Araceae) is a plant species with extremely small populations (PSESP) and an important economic crop endemic to dry-hot valleys along the Jinsha River. In order to gain information for sustaining the development and conservation of A. albus, we studied the genetic diversity and population structure of this species using microsatellite markers (SSR). In this study, we analysed 364 individuals belonging to 24 populations, including four wild populations and three ex-situ cultivated populations, collected in the provinces Yunnan, Sichuan and Hubei. Results The population genetic analyses indicated that A. albus possesses moderate genetic diversity with the percentage of polymorphic loci (PPL) from 69.23 to 100%, an expected heterozygosity (He) of 0.504 and an average Shannon’s Information Index (I) 0.912. Analysis of molecular variance (AMOVA) indicated that most of the variance (71%) resided within populations and the estimated gene flow (Nm) was 0.61. The results of UPGMA cluster tree, STRUCTURE analyses together with the Mantel test (R2 = 0.352, P < 0.01) indicated that geographically closely located populations are clustered together with some exceptions. Conclusions Our results showed that A. albus still possesses moderate genetic variation in most of the studied populations, and for now, most cultivated populations were naturally distributed but still some reintroduction exists. For sustaining the present genetic variation, some protections measures are necessary for the wild populations and also for the cultivated ones with high genetic diversity.